2011
DOI: 10.3813/aaa.918439
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Blocked Force at Impact of Japanese Rubber Ball Source

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…Hiramatsu [29] tested a three-story full scale school within type A floor, using three different sources: car tyre, rubber ball and tapping machine. The results show a similar ISO tapping machine frequency trend compared to previous studies, but the other two sources, as expected [30]- [33], provide very different behaviours; the author concludes that the best source for A type is the car tyre conversely to Bettarello's outcomes [6].…”
Section: Type Asupporting
confidence: 76%
See 1 more Smart Citation
“…Hiramatsu [29] tested a three-story full scale school within type A floor, using three different sources: car tyre, rubber ball and tapping machine. The results show a similar ISO tapping machine frequency trend compared to previous studies, but the other two sources, as expected [30]- [33], provide very different behaviours; the author concludes that the best source for A type is the car tyre conversely to Bettarello's outcomes [6].…”
Section: Type Asupporting
confidence: 76%
“…Hammer [15], [16] investigated the structure using analytical models, considering the excitation force and the interaction of ISO tapping machine on lightweight floors [30]. Their conclusions report the following considerations:…”
Section: Type Bmentioning
confidence: 99%
“…Refs. [12,23]]. The main features are (a) contact time of approximately 20 ms, and (b) an asymmetric approximation to a half-sinusoid with ripples on the first part of the curve where there is increasing force and a smoother curve for the decreasing force.…”
Section: Force Plate Measurementsmentioning
confidence: 99%
“…Schoenwald et al [12] used a simplified analytical model to calculate the force that was applied by the rubber ball when impacting a rigid surface. Comparison with measurements indicated that the rubber ball was a significantly more complex source than the analytical model of a hollow spherical shell.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of building acoustics, human walking has been simulated using an impact source such as a tapping machine or a heavy/soft impact source [31]. It has been suggested that a heavy/soft impact source is a good representative of human walking in terms of mechanical impedance and impact force as well as subjective similarity [38][39][40] 0.97 for Wb, Wk, and Wm (p<0.01), and 0.96 for Wg (p<0.01). This implies that the relative importance of vibration with different floors might be obtained using a heavy/soft impact source instead of field measurements with humans walking.…”
Section: Prediction Of Vibration Perception Using a Standard Impact Smentioning
confidence: 99%